Quality of life in enlargement countries Third European Quality of Life Survey - Former Yugoslav Republic of Macedonia - European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2013)
This document provides background information to the profiles on quality of life in seven EU enlargement countries that are published as individual papers - Croatia, Iceland, Kosovo, Montenegro, Serbia, Turkey and the former Yugoslav Republic of Macedonia. It identifies the countries that participated in the survey, explains survey characteristics, and provides definitions of indicators reported in individual country papers. In 2011-2012, when the third European Quality of Life Survey (EQLS) was carried out, the European Union consisted of 27 Member States. It enlarged to 28 when Croatia joined on 1 July 2013.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- Former Yugoslav Republic of Macedonia; Former Yugoslav Republic of Macedonia -- Social conditions -- 21th century; Electronic books